Wireless Sensor Network in Precision Agriculture - Jasmine Lizy, P; Chenthalir Indra, N (International Journal of Computer Sciences and Engineering, 2020)
Wireless sensor Network is a self-organizing Network. WSN can be deployed in various environments for monitoring purpose. WSN has major applications on health monitoring, military surveillance, weather monitoring, agriculture, etc. In recent decade wireless sensor network implemented in agriculture field are encouraged in many researches. WSN in precision agriculture help to measure different environmental factors such as humidity, temperature, soil moisture, PH value of soil,etc. This precision agriculture helps to enhance the crop quality.Utilizing wireless sensor technologies and management tools can help to identify various diseases in crops, excess usage of pesticides, etc. This paper proposes the efficient use of sensor network in precision agriculture to help the farmers. This paper presents agricultural field where the sensors are used and the different types of sensors used in precision agriculture, also it suggests the environmental factors influencing agriculture.